2018
DOI: 10.1186/s12913-018-3760-z
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based approach to understanding the competency development needs of the health service management workforce in Australia

Abstract: BackgroundCompetent managers are essential to the productivity of organisations and the sustainability of health systems. Effective workforce development strategies sensitive to the current competency development needs of health service managers (HSMs) are required.PurposeTo conduct a 360° assessment of the competence of Australian HSMs to identify managerial competence levels, and training and development needs.MethodsAssessment of 93 middle-level HSMs from two public hospitals (n = 25) and five community hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 31 publications
(46 reference statements)
9
49
0
Order By: Relevance
“…Less than 4% of managers indicated any of the six competencies being unimportant or very unimportant. This confirms the 'existence of core management competencies across management levels and position theory' [35,27,28]. The confirmation of the inadequate acquisition of competency C2 and C6 prior to taking up the current management positions are confirmed by the low levels of self-perceived competence when managers were asked to rate their competency level against each management competency using the validated MCAP competency scale [27].…”
Section: Management Competency Self-perception -Importance Acquisitisupporting
confidence: 68%
“…Less than 4% of managers indicated any of the six competencies being unimportant or very unimportant. This confirms the 'existence of core management competencies across management levels and position theory' [35,27,28]. The confirmation of the inadequate acquisition of competency C2 and C6 prior to taking up the current management positions are confirmed by the low levels of self-perceived competence when managers were asked to rate their competency level against each management competency using the validated MCAP competency scale [27].…”
Section: Management Competency Self-perception -Importance Acquisitisupporting
confidence: 68%
“…Less than 4% of managers indicated any of the six competencies being unimportant or very unimportant. This confirms the 'existence of core management competencies across management levels and position theory' [27,28,35]. Ignoring their importance, not all managers believed that they had acquired the required competencies prior to taking up the current management positions.…”
Section: Management Competency Self-perceptionimportance Acquisitionsupporting
confidence: 62%
“…Overall, C2 and C6 were the only two competencies which received mean competency scores lower than four amongst all managers. A similar study conducted with senior managers in public hospitals and community health services in Australia also confirmed C2 and C6 were two of the competencies in which managers were least confident by self-competency assessment [35].…”
Section: Management Competency Self-perceptionimportance Acquisitionmentioning
confidence: 59%
“…The six core competencies that have been included in the MCAP framework as detailed earlier in the paper have been well discussed in the literature and agreed by recent studeis. Hence, there is no doubt of their importance to be included as core competenceis for health service managers to acquire in order to perform their managerial responsibilities effectively [11,35,53]. Although the MCAP framework did incorporate behavioural items associating with the competency of Professionalism, the systematic literature review and the mapping confirmed the neccessity of including Professionalism as a separate competency for health service managers.…”
Section: Figure 3 Insert Herementioning
confidence: 95%
“…in-service training; in-house use of mentors and study groups; offsite intensive training, and seminars and conferences for acheive it [55]. To facilitate managerial development, It has been suggested that competency-based education and training for health services managers be established and adopted [53].…”
Section: Figure 3 Insert Herementioning
confidence: 99%